1991
DOI: 10.1080/00049158.1991.10674562
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between growth strain and rate of growth in 22 year-oldEucalyptus grandis

Abstract: Using electronic strain gauges, longitudinal peripheral growth strain was measured at 1.6 m height in fifty 22-year-old plantation grown trees of Eucalyptus grandis (Hill) Maiden.The extent of peripheral growth strain was not found to be related to rate of growth. This result and measurements of internal growth strains in five 32-year-old trees suggested that splitting of wood during conversion would be less likely in trees with faster rates of growth, due to a lower longitudinal strain gradient along a radius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
5
0
2
Order By: Relevance
“…This finding concurs with previous data showing that growth stress is not affected by growth rate in fast-growing species younger than 15 years. 8,9,14 Because planted eucalypts with large diameters are reported to have lower released strain, 16 Fig. 2 could be interpreted as showing that trees larger than 30 cm in diameter had lower strain, although the difference is statistically insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…This finding concurs with previous data showing that growth stress is not affected by growth rate in fast-growing species younger than 15 years. 8,9,14 Because planted eucalypts with large diameters are reported to have lower released strain, 16 Fig. 2 could be interpreted as showing that trees larger than 30 cm in diameter had lower strain, although the difference is statistically insignificant.…”
Section: Resultsmentioning
confidence: 99%
“…While peripheral tensile stresses are present in upright trees (Timell 1987;Wilkins & Kitahara 1991) such stresses can be considered to be in equilibrium and as prestressing in the tree stem. If however the stems are bent, it is suggested that the reaction wood mechanisms as outlined above will come into play and right the stem.…”
Section: How Trees Stay Uprightmentioning
confidence: 99%
“…However, work on growth stresses in tropical forest species is limited. From the literature, it is evident that growth stress and growth rate are not related (Boyd, 1980;Okuyama et al 1981;Wilkins & Kitahara, 1991;Wahyudi et al, 1999Wahyudi et al, , 2000Wahyudi et al, & 2001. Growth stress was not related to either tree age or diameter (Jacob, 1945).…”
Section: Introductionmentioning
confidence: 99%